Walking the bones - Silvis, Randall, 1950- (Silvis, Randall, 1950- Ryan DeMarco mystery., 2018)
"Ryan DeMarco's decision to take a leave of absence from the Pennsylvania State Police was a surprise to everyone--but a year after the homicide case in which DeMarco put a bullet in the heart of the madman who killed his only friend's family, he can't face another day on the force. Now, heading out on an extended road trip with Jayme, his former colleague and present girlfriend, DeMarco is ready to let his old wounds heal. But when DeMarco and Jayme arrive in Jayme's tiny hometown for her grandmother's funeral, they're quickly recruited to help solve a long-dead case involving seven skeletons of young girls. DeMarco's instinct is to take to the open road again, but Jayme's desire to stay and help prevails. The investigation leads DeMarco deep into the heart of the Daniel Boone National Forest, an ordeal that frightens and nearly kills him, but which eventually results in the identification of the murderer, closure for the small community, and personal redemption for DeMarco as he allows himself to love again"--